An upstream enhancer and a negative element in the 5' flanking region of the human urokinase plasminogen activator gene. - Verde, P (1988)
The 5' flanking region of the human urokinase (uPA) gene has been fused to the reporter chloramphenicol acetyl transferase (CAT) gene and its activity assayed by transfection in two human cell lines. Progressive deletions of the uPA regulatory region from the 5' end maintain a high level of expression provided at least 1870 (in A1251 cells) or 1963 (in HFS10 cells) nucleotides of the 5' flanking region are retained. A DNA fragment from -2350 to -1824 has enhancer properties, stimulating transcription of an enhancerless SV40 early promoter independently of orientation and distance. Internal deletions that still retain the enhancer element reveal the presence of negative cis-acting sequences between -1824 and -1572. Their removal, in fact, increases uPA transcriptional activity. Differences of expression of the uPA-CAT fusion genes in the two cell lines are also observed, indicating the presence of cell-specific cis-acting sequences.